Odpowiedź :
Równanie A:
[tex]3x - 4 = 8 \ \ \ \ \ | +4\\3x = 12 \ \ \ \ \ |:3\\x = 4[/tex]
Równanie B:
[tex]5x - 6 = x + 8 \ \ \ \ \ |+6\\5x = x+14 \ \ \ \ \ |-x\\4x = 14 \ \ \ \ \ |:4\\x = \frac{7}{2}[/tex]
Równanie C:
[tex]3(x + 4) = 2x - 3\\3x +12 = 2x-3 \ \ \ \ \ \ \ \ |-12\\3x = 2x-15 \ \ \ \ \ \ \ |-2x\\x = -15[/tex]
a)3x-4=8
3x=8+4
3x=12 /:3
x=4
b)5x-6=x+8
5x-x=8+6
4x=14 /:4
x=3,5
c)3(x+4)=2x-3
3x+12=2x-3
3x-2x=-3-12
x=-15
3x=8+4
3x=12 /:3
x=4
b)5x-6=x+8
5x-x=8+6
4x=14 /:4
x=3,5
c)3(x+4)=2x-3
3x+12=2x-3
3x-2x=-3-12
x=-15